The soil-plant-atmosphere continuous as an integrating model of forest ecophysiology - Gil-Pelegrin, E.; Aranda, I.; Peguero-Pina, J. J.; Vilagrosa, A. (Forest Systems, 2005)
The great complexity showed by plants in their structure and performance makes neccesary the development of theoretical models that include all aspects of this question. The SPAC model is a good theoretic and functional approach because it analyzes water in the plant from soil as source to atmosphere as sink, taking into account the characteristics of the structure of the plant, and the edaphic and atmospheric limitations to water transport. The breaking of this continuous in whatever place, by several causes (stomatal regulation, embolism processes, etc.), prevents the optimal performance of the plant and, therefore, limits the possibilities of survival.